Electricity Consumption-Economic Growth Nexus: The Ghanaian Case - Adom, Philip Kofi (International Journal of Energy Economics and Policy, 2011)
Research into the electricity-economic growth nexus has important implications for energy conservation measures and environmental policy. However, results from the energy-economic growth nexus have been mixed in the literature on Ghana. This posses serious problems for the country’s energy policy. Much research is thus, required to establish the direction of causality between energy and economic growth. Nonetheless, less evidence is available for Ghana. It is against this background that this study seeks to investigate the direction of causality between a type of energy, electricity, and economic growth to add to the existing argument in the literature. The Toda and Yomamoto Granger Causality Test was used to carry out the test of causality between electricity consumption and economic growth from 1971 to 2008. The results obtained herein revealed that there exists a unidirectional causality running from economic growth to electricity consumption. Thus, data on Ghana supports the Growth-led-Energy Hypothesis. The results imply that electricity conservation measures are a viable option for Ghana. Keywords: Ghana; Real GDP per capita; Electricity consumption; Toda and Yomamoto; Granger Causality Test; Bounds cointegration JEL Classifications: Q400; Q430